What Determines M&A Legal and Financial Advisors' Competitiveness in an International Financial Centre: Using China's Going Out Policy as a Natural Experiment - Bryane Michael; Dariusz Wojick; Douglas W. Arner; Wilson Tong; Chen Lin; Simon Zhao (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Roughly 60% of all publically announced advisors to China's “Going Out” M&A transactions from 2000 to 2014 were from international financial centres (representing over 70% of deal value). Why did advisors, located so far away from both acquirer and target, manage to dominate the M&A advisory market in the early stages of the “Going Out” policy? What can we learn from the smaller advisors located outside of these financial centres who managed to capture a growing share of this business in “Going Out's” more recent stages? In this paper, we hypothesize the existence of a “legal complexity externality” that had the effect of increasing a financial centre's ability to attract international business. We look at the way Going Out advisors have responded to advisory opportunities using what management theorists call “blue ocean strategy.” We show that relationships across geography changed, as large global advisors lost their share of advisory business to advisors outside of international financial centres due to the interplay of these legal complexity externalities and blue ocean strategies. As cities helps foster changes in the law governing Going Out transactions – and as financial and legal advisors adapted their strategies to compete – cities gained or lost Going Out business. We provide 5 recommendations to existing and aspiring international financial centres looking to capture a larger share of global M&A and other investment advisory business.
Keywords: K40; G34; 330; law schools; international financial centre; mergers and aquisitions; Going Out Policy; legal complexity externality; professional services; Takeover; China; Experts